HUBUNGAN PENGETAHUAN WARNA DENGAN HASIL RIAS WAJAH PESTA PADA SISWA TATA KECANTIKAN KULIT SMK NEGERI 1 BERINGIN - Yuspa Hanum; Ramadhani Ramadhani (Universitas Negeri Medan, 2018)
ABSTRACTThis study aims to determine the knowledge of colors, the results of party makeup and find out the relationship between the knowledge of colors and the results of student makeup on the skin. The population in the study were 30 people. The results of the average score of color knowledge in students amounted to 34.73 with a tendency level categorized as high with the details of 8 students (26.7%) having high knowledge, 22 students (73.3%) having sufficient knowledge. On observing party makeup results obtained an average score of 29.63 with a tendency level categorized high with the details of 14 students (46.7%) getting high makeup results, 16 students (53.3%) getting the results of makeup that enough.Keywords: Knowledge of Colors, Results of Party Makeup